AVALIAÇÃO DO CONHECIMENTO DO CONSUMIDOR SOBRE AS INFORMAÇÕES OBRIGATÓRIAS DAS ETIQUETAS DOS PRODUTOS TÊXTEIS - Franco, Márcia Rosa Pereira (2009)
In this study it was looked for to evaluate the consumer's knowledge on the obligatory information of the labels of the textile products. As for the methodological aspects to present research is classified as being of field, through the use of a questionnaire previously elaborated, addressed the consumers of six States of Brazil. In the analysis of the results it was looked for to identify the composition information and conservation treatment, obligatory in the textile products, they configured a criterion of value for the consumer, being frequently observed, or no, in the action of the purchase; to determine the consumer's reliability concerning the information contained in the labels of the textile products, as well as his knowledge degree on the symbols of the conservation treatment, obligatory, expressed in the same ones; if the mark 'INMETRO', when expressed in the textile products, it contributes to the socket of the consumer's decision in the action of the purchase; and finally, to propose a Program of Evaluation of the Conformity to substitute the current technical regulations imposed by the State, in what he refers to the textile products, for a symbol of identification of the conformity. It was ended that the mark 'INMETRO', when expressed in the textile products, it contributes fundamentally for the socket of the consumer's decision in the action of the purchase.